Hidden treasures of the Himalayas: Tibetan manuscripts, paintings and sculptures of Dolpo - Heller, Amy (Serindia Publ., 2009)
The history of Dolpo and Bicher -- Reconstructing the history of Bicher village -- Nesar Temple and its contents -- Illuminations and dedications in the Nesar manuscripts -- Nesar Temple in the context of village temples in Dolpo and western Nepal